Определение энергетического спектра нейтронов в ядерной фотоэмульсии внутри уран-свинцовой сборки электроядерной установки - Д, Отгонсурэн; Р, Тогоо; Б, Тумэндэмбэрэл (Scientific transaction of the National University of Mongolia. Physics, 2022)
Measurements of the energy spectrum of neutrons in the volume of the uranium-lead assembly of the installation “Energy plus Transmutation” are carried out by means of registration of recoil protons in highly sensitive nuclear emulsions. There is a maximum in this spectrum at about (1.0±0.1) MeV, its center of mass is located in the region of 5-7 MeV depending on the cut-off energies used.